Unveiling depression—A cross-sectional study of college students in Amritsar District - Shalinder Kaur; Simmi Oberoi; Rohit Batish; Shyam Sunder Deepti; Mohan Lal; Balpreet Kaur (Journal of Family Medicine and Primary Care)
Background: Mental health problems are becoming more and more frequently a burden on modern societies. A gradually evolving way of life, particularly in westernizing nations like India, could be attributed to a variety of causes, including shifting societal support, partnerships, and family bonding. Young People having conflicts with parents and friends, academic pressure and getting inconsistent sleep, and being in an environment where alcohol and drugs are more readily available could all be risk factors for depression. Objectives: 1. To determine the prevalence of depressive symptoms among professional and non-professional course students. 2. To assess the factors associated with depressive symptoms in these students. Material and Methods: This cross-sectional study was conducted from 1 January 2014 to 31 December 2014 in Amritsar district among 1470 students of various educational institutes. After IEC approval, the study was carried out after obtaining written consent from students aged 18 to 24 years. They were interviewed using a pre-validated, semi-structured questionnaire that included Depression Factors Questionnaire, Socio-demographic section and the Patient Health Questionnaire-9 (PHQ-9). Statistical analysis was performed using Chi-square tests. Results: Majority (82.9%) were from non-professional degree courses. Nearly half of the study population i.e. 761 (51.8%) belonged to Hindu religion. Depression was among the highest among overweight (25%) as compared to normal and underweight students. Depression was also observed to be higher among those respondents who became anxious on getting a new assignment (24.7%) as compared to those who could do the assignment on time (12.7%). Conclusion: Students who had good friends and satisfactory relationships with their parents and neighbors experienced lower levels of depression compared to those who did not.